Neural specialization for speech in the first months of life. Issue 5 (27th February 2014) - Shultz, Sarah; Vouloumanos, Athena; Bennett, Randi H.; Pelphrey, Kevin
Abstract How does the brain's response to speech change over the first months of life? Although behavioral findings indicate that neonates' listening biases are sharpened over the first months of life, with a species‐specific preference for speech emerging by 3 months, the neural substrates underlying this developmental change are unknown. We examined neural responses to speech compared with biological non‐speech sounds in 1‐ to 4‐month‐old infants using fMRI. Infants heard speech and biological non‐speech sounds, including heterospecific vocalizations and human non‐speech. We observed a left‐lateralized response in temporal cortex for speech compared to biological non‐speech sounds, indicating that this region is highly selective for speech by the first month of life. Specifically, this brain region becomes increasingly selective for speech over the next 3 months as neural substrates become less responsive to non‐speech sounds. These results reveal specific changes in neural responses during a developmental period characterized by rapid behavioral changes.